Immuno-enhancing effects of fruit of Actinidia polygama in macrophages - Hyun Ji Eo (Taylor & Francis Group, 2021)
In this study, we evaluated the functionality of water extracts from the fruit of Actinidia polygama (APF) in macrophages. The APF is a medicinal plant belonging to Actinidiaceae, it has been reported to exert anti-inflammatory, analgesic and hypouricemic activities. However, the potential mechanism for the immune activation of the APF is still insufficient. So, we evaluated whether APF exerts immune activation activities and elucidated its potential mechanism in macrophages. The APF dose-dependently increased the production of immunomodulators in macrophages. The inhibition of Toll-like receptor 4 (TLR4) blocked APF-mediated production of immunomodulators in RAW264.7 cells. In addition, APF-mediated production of immunomodulators was attenuated by MAPKs and NF-κB inhibition in RAW264.7 cells. Also, we analyzed the sugars content of the APF. The contents of glucose, galactose and fructose were 3597, 904, 7582 mg/L, respectively. These results suggest that the APF may have great potential for the development of immunomodulatory drugs.